Modern Imaging Methods in the Diagnosis of Neurodegenerative Diseases - Pietrukaniec , Paulina Dorota; Omasta , Bartosz; Kamińska-Omasta, Katarzyna; Krupa, Olga; Rybak, Daria; Romańczuk, Kuba Borys; Czerska, Magdalena Agata; Stolarczyk, Szymon Przemysław; Wójcik, Zofia Martyna; Furtak, Kinga (Quality in Sport, 2025)
Neurodegenerative diseases, such as Alzheimer’s, Parkinson’s and other forms of dementia, represent a major global health challenge. Early diagnosis and monitoring of disease progression are key to effective management of these conditions. Advanced brain imaging techniques, such as magnetic resonance imaging (MRI), positron emission tomography (PET), single photon emission tomography (SPECT) and functional magnetic resonance imaging (fMRI), play a key role in the diagnosis and monitoring of neurodegenerative diseases. This article outlines the various imaging methods, their application in the context of major neurodegenerative diseases, as well as the advantages and limitations of each. In addition, the prospects for the development of these technologies, including the use of artificial intelligence and new biomarkers in diagnosis, are also discussed.